Subsequent Primary Cancers of the Digestive System Among Childhood and Adolescent Cancer Survivors From 1975 to 2015 in the United States. (13th May 2021) - Liu, Jason J.; Chen, Chuan-Yu; Giovannucci, Edward; Wu, Chun-Ying
Abstract : INTRODUCTION: Among survivors from first primary cancers that occurred during childhood and adolescence, their risks of developing subsequent primary digestive system cancers are not well understood. Therefore, we conducted the largest and most comprehensive analysis examining risks for diverse types of digestive system cancers after survival from a wide variety of first primary childhood and adolescent cancers. METHODS: We identified 41, 249 patients diagnosed with first primary cancer from 1975 to 2015 before 20 years of age from 9 Surveillance, Epidemiology and End Results Program registries. Standardized incidence ratios (SIRs) and absolute excess risks (AERs) for digestive system cancers were calculated controlling for age, sex, race, and calendar year. RESULTS: Among 41, 249 cancer survivors, 133 developed subsequent primary digestive system cancer, with a median digestive system cancer diagnosis age of 37 years. The SIR and AER for any digestive system cancer were highest among survivors of bone cancer, lymphoma, and neuroblastoma. Among survivors from any first primary cancer, the SIR was significantly elevated for cancer of the esophagus, stomach, small intestine, large intestine, liver, and pancreas, whereas the AER was highest for large intestine cancer. DISCUSSION: Childhood and adolescent cancer survivors diagnosed from 1975 to 2015 have significantly elevated risks of digestive system cancers compared with the US general population. Our detailed findings may contribute to surveillance recommendations of childhood and adolescent cancer survivors and promote future studies to further understand mechanisms by which having various first primary cancers lead to subsequent primary digestive system cancers.